Self‐Expectoration of Airway Stent Following Chemoimmunotherapy in Extensive Disease Small Cell Lung Cancer - Keisuke Shiraha; Yuki Takigawa; Ken Sato; Mayu Goda; Suzuka Matsuoka; Hiromi Watanabe; Kenichiro Kudo; Keiichi Fujiwara; Takuo Shibayama (Respirology Case Reports, 2025)
ABSTRACT A 76‐year‐old man with extensive disease small cell lung cancer underwent airway stenting for right bronchus intermedius stenosis. The stent self‐expectorated after initiating chemoimmunotherapy due to tumour shrinkage. Clinicians should be aware of the possibility of stent migration in malignant central airway obstruction patients who respond to chemotherapy.